Continuous professional development in higher education: A systematic review of its conceptualizations, trends and challenges (2011- 2020) - Medhanit Adane Solomon; Amare Asgedom Gebremedhin; Kassahun Weldemariam Tigistu (Bahir Dar Journal of Education, 2023)
The purpose of this systematic review is twofold. On the one hand, the authors investigate the conceptualizations and associated trends in staff Continuous Professional Development (CPD) in higher education. On the other hand, they explore the challenges that hinder academic staff from engaging in CPD in higher education.  To this end, the authors employ Preferred Reporting Items for Systematic Reviews and Meta-Analyses-PRISMA. The findings reveal that there are varied conceptualizations of CPD in higher education which include: activities and interventions taken aimed at improving knowledge, skills, and attitudes of academics. Likewise, the trends of CPD in higher education vary in form, focus area/content, strategy, and expected outcomes. The challenges hindering academics range from individual academics' attitude to their respective institution to the national policies that govern higher education. Finally, we argue that effective CPD in higher education requires a systematic, comprehensive, and well-established policy-led approach to staff development.